2021
DOI: 10.1371/journal.pgen.1009771
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific mitochondrial stress induced by Multiple Mitochondrial Dysfunctions Syndrome 1 pathogenic mutations modeled in Caenorhabditis elegans

Abstract: Multiple Mitochondrial Dysfunctions Syndrome 1 (MMDS1) is a rare, autosomal recessive disorder caused by mutations in the NFU1 gene. NFU1 is responsible for delivery of iron-sulfur clusters (ISCs) to recipient proteins which require these metallic cofactors for their function. Pathogenic variants of NFU1 lead to dysfunction of its target proteins within mitochondria. To date, 20 NFU1 variants have been reported and the unique contributions of each variant to MMDS1 pathogenesis is unknown. Given that over half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 106 publications
(213 reference statements)
2
14
0
Order By: Relevance
“…Our prior results ( Kropp et al, 2021a ) and those presented here indicate that patient-specific variants of nfu-1 , both of which are reduction- or loss-of-function alleles, result in neuromuscular dysfunction, with each nfu-1 variant resulting in distinct neuromuscular defects ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our prior results ( Kropp et al, 2021a ) and those presented here indicate that patient-specific variants of nfu-1 , both of which are reduction- or loss-of-function alleles, result in neuromuscular dysfunction, with each nfu-1 variant resulting in distinct neuromuscular defects ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 66%
“…We previously demonstrated that patient-specific MMDS1 variants in the C. elegans gene nfu-1 display mitochondrial stress, including morphological and functional impairments, in multiple tissues ( Kropp et al, 2021a ). Because mitochondrial stress can result in movement defects due to dysfunction in the neuromuscular system, we assessed the motility of nfu-1 variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, another siderophore 2′2-bipyridyl (BP) has been reported to enhance mitochondrial degradation through a PINK1, PDR-1, and DCT-1 dependent mechanism by triggering a hypoxia-like response in C. elegans ( Schiavi et al, 2015 ). Additionally, BP treatment has also been shown to promote longevity through the mitophagy induction mechanism in C. elegans ( Kropp et al, 2021 ). Several studies have demonstrated mitophagy-inducing properties of these iron chelators, further investigations are required to understand their underlying mechanisms of actions and therapeutic potential.…”
Section: Receptor Mediated Mitophagymentioning
confidence: 99%